2017
DOI: 10.3324/haematol.2016.160754
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding risk of surgery and its prevention in patients with inherited platelet disorders

Abstract: Excessive bleeding at surgery is a feared complication in patients with inherited platelet disorders. However, very few studies have evaluated the frequency of surgical bleeding in these hemorrhagic disorders. We performed a worldwide, multicentric, retrospective study to assess the bleeding complications of surgery, the preventive and therapeutic approaches adopted, and their efficacy in patients with inherited platelet disorders: the Surgery in Platelet disorders And Therapeutic Approach (SPATA) study. We ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 36 publications
2
106
0
6
Order By: Relevance
“…A retrospective analysis of bleeding and transfusion with invasive procedures in a heterogenous group of 423 patients with inherited platelet disorders found excessive bleeding risk in those with Bernard-Soulier syndrome, autosomal variant Glanzmann thrombasthenia, and Hermansky-Pudlak syndrome. 36 Bleeding was twice as common in inherited platelet function disorders (24.8% of procedures) compared with inherited thrombocytopenias (13.4% of procedures). The latter were associated with infrequent surgical bleeding until the platelet count was below 68Â10 9 L À1 .…”
Section: Inherited Platelet Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective analysis of bleeding and transfusion with invasive procedures in a heterogenous group of 423 patients with inherited platelet disorders found excessive bleeding risk in those with Bernard-Soulier syndrome, autosomal variant Glanzmann thrombasthenia, and Hermansky-Pudlak syndrome. 36 Bleeding was twice as common in inherited platelet function disorders (24.8% of procedures) compared with inherited thrombocytopenias (13.4% of procedures). The latter were associated with infrequent surgical bleeding until the platelet count was below 68Â10 9 L À1 .…”
Section: Inherited Platelet Disordersmentioning
confidence: 99%
“…The latter were associated with infrequent surgical bleeding until the platelet count was below 68Â10 9 L À1 . 36…”
Section: Inherited Platelet Disordersmentioning
confidence: 99%
“…that the risk of spontaneous bleeding events in severely thrombocytopenic patients is not directly related to the platelet count, 19,20 and that the risk of surgical or obstetric bleeding is higher in patients with inherited disorders of platelet function than in inherited disorders of platelet numbers. 21,22 Also, in another recent study, it was found that although there was an increased incidence of bleeding events during delivery in women with inherited thrombocytopenia and a platelet count of <50 × 10 9 L −1 , the increased incidence did not seem to be linearly correlated with platelet counts, as the odds ratio (OR) for bleeding events showed a nonsignificant trend towards lower incidences of bleeding in the tertile of platelets with a platelet count of 49-80 × 10 9 L −1 in comparison with patients with a platelet count of > 80 × 10 9 L −1 . 23 These observations indicate that clinical decision making needs to be based on knowledge regarding both quantitative and qualitative defects in primary hemostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Platelet function disorders (PFD) are clinically important bleeding disorders that are particularly challenging for clinical laboratories to diagnose. Many PFD are associated with increased bleeding scores and increased risks for bleeding . Commonly, laboratory tests for PFD are performed to investigate unexplained bruising, heavy menstrual bleeding, prolonged and excessive bleeding from cuts, nosebleeds, and dental and surgical procedures .…”
Section: Introductionmentioning
confidence: 99%